Application and Problems of Low-altitude Remote Sensing Technology in Geological Disaster Monitoring - Ren, Jie (Transactions on Environment, Energy and Earth Sciences, 2024)
The geological structure of our country is complex, with a wide area of mountains and hills, and once a geological disaster occurs, it can cause huge damage. Therefore, researching how to monitor geological disasters has significant practical significance. The paper summarizes the different techniques used by various scholars to monitor geological disasters using low-altitude remote sensing. Low-altitude remote sensing has emerged as a powerful tool for capturing high-resolution spatial and temporal data, offering real-time monitoring capabilities that traditional methods, such as satellite imaging, often cannot match. The current technical issues and prospects, the advantages and disadvantages of different technologies, and the direction for improvement are discussed. Combining multiple disciplines, such as geology, remote sensing, and geographic information systems (GIS), can better understand the underlying causes of these disasters and develop more accurate monitoring methods. It is significant to improve the response speed of disaster prediction by building a complete prediction chain. With the continuous development of monitoring systems, we can reduce the harm caused by geological disasters to the lives and property of the Chinese people.